2019
DOI: 10.1152/japplphysiol.00594.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity affects acute neurotrophic and neurophysiological responses poststroke

Abstract: Aerobic exercise may acutely prime the brain to be more responsive to rehabilitation, thus facilitating neurologic recovery from conditions like stroke. This aerobic priming effect could occur through multiple mechanisms, including upregulation of circulating brain-derived neurotrophic factor (BDNF), increased corticospinal excitability, and decreased intracortical inhibition. However, optimal exercise parameters for targeting these mechanisms are poorly understood. This study tested the effects of exercise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
148
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(165 citation statements)
references
References 60 publications
(102 reference statements)
7
148
2
2
Order By: Relevance
“…14 A secondary analyses found that an exercise intensity around the onset of blood lactate accumulation was the optimal threshold for discriminating large acute BDNF responses. 14 While these results provide preliminary evidence that BDNF could potentially mediate some intensity-dependent effects of exercise on neurologic function, there are also several other less-studied molecules that could be involved. For example, vascular endothelial growth factor (VEGF) and insulin-like growth factor 1 (IGF1) are 2 additional neurotrophins that accumulate in human blood during exercise, 15,16 and have some evidence of intensity-dependence.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…14 A secondary analyses found that an exercise intensity around the onset of blood lactate accumulation was the optimal threshold for discriminating large acute BDNF responses. 14 While these results provide preliminary evidence that BDNF could potentially mediate some intensity-dependent effects of exercise on neurologic function, there are also several other less-studied molecules that could be involved. For example, vascular endothelial growth factor (VEGF) and insulin-like growth factor 1 (IGF1) are 2 additional neurotrophins that accumulate in human blood during exercise, 15,16 and have some evidence of intensity-dependence.…”
Section: Introductionmentioning
confidence: 87%
“…The purpose of this study was to determine the effect of exercise intensity on acute circulating VEGF, IGF1, and cortisol responses poststroke, using the same data set and serum samples as a previous BDNF analysis. 14 We hypothesized that high-intensity interval training (HIT), whether performed on a treadmill (HIT-treadmill) or seated stepper (HIT-stepper), would elicit significantly greater acute increases in VEGF and IGF1 compared with moderateintensity continuous exercise (MCT-treadmill). We also hypothesized that there would be no significant betweenprotocol difference in cortisol response, based on the limited evidence of psychological stress found in a previous qualitative assessment of treadmill HIT after stroke.…”
Section: Bdnf Is An Abundantmentioning
confidence: 99%
See 2 more Smart Citations
“…intermittent) [26]. It was hypothesized that HI would increase corticospinal excitability compared to MOD in low fit young adults, as higher intensity exercise evokes increased BDNF [16][17][18]27] and IGF-1 [14] levels more so than moderate-intensity exercise.…”
Section: Introductionmentioning
confidence: 99%